Pelatihan Proses Mencipta Tari Melalui Pengelolaan Gerak dan Pemanfaatan Digital Audio Software di Lembaga Budaya Aceh Nusantara, Banda Aceh - Prasika Dewi Nugra; Sabri Gusmail; Benni Andiko (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The process of creating dance cannot exclude motion as the main medium for expressing dance. So that empirical experience is needed in the creative process of creating, including basic theoretical knowledge and practical skills in the management of motion and its supporting elements. Knowledge and insight into the science of choreography is felt to be given to non-formal institutions such as communities/art studios as a form of synergy between agencies in an effort to promote culture as stated in Law No. 5 of 2017 concerning the Advancement of Culture. This article is part of Community Service involving the Budaya Aceh Nusantara (Buana). The priority of partner problems is the lack of insight and skills of human resources in the process of creating new works, especially innovative dances originating from traditional arts. Solutions to solving partner problems are carried out in the form of training including dance movement management training and the process of creating dance accompaniment music in the form of skill transfer or providing joint creation experience. The training was conducted using Jacqueline Smith's choreographic approach and the process of creating accompaniment music through digital audio software processing techniques. The training methods include: planning, implementing (acting), monitoring or observing and assessment (reflecting or evaluating). From the results of the training, it can be seen that the participants' skills increase in the management of motion and the use of audio software in the process of creating dances. On the other hand, the training module becomes reading material that the community can always use as a reference and guide in independent practice. The implementation of the training is expected to have a significant impact in increasing the productivity of creating dances at the Buana communities